Effect of five rootstocks in flowering, fructification and maturity in orange "frost valencia" citrus sinensis (l.) obs. in palmira, the cauca valley (1992)
The work was made at Instituto Colombiano Agropecuario, Palmira in the Cauca Valley. It was considered under observation twenty citric trees over five rootstocks: Citrumelo 4475, Citrus amblycarpa, Citrange yuma, Trifoliado por Ruby Or and Mandarina Cleopatra. Flower development, intensity of flower and fruit production, thicken percentage, fruit's development, fruits falled percentage, maduration process and number and weight at harvested fruits was evaluated. Flowering is induced between 15-30 days after any rain. The maximum fruit production was between five and six months after maximum precipitation. The rootstocks are different in maturity epoch, fruit's production; however there were not great differences in potential production (17-20%).